Growth, spectroscopy and continuous-wave laser performance of Nd3+:LiLu0.65Y0.35F4 crystal. (2nd March 2018) - Demesh, M P; Kurilchik, S V; Gusakova, N V; Yasukevich, A S; Kisel, V E; Nizamutdinov, A S; Marisov, M M; Aglyamov, R D; Korableva, S L; Naumov, A K; Semashko, V V; Kuleshov, N V
Abstract: A mixed fluoride crystal of LiLu0.65 Y0.35 F4 doped with Nd 3+ ions was grown by the Bridgman–Stockbarger method. Polarized absorption and luminescence spectra as well as luminescence lifetime were measured at room temperature. Emission probabilities, branching ratios and radiative lifetime were studied within the Judd–Ofelt theory and the emission cross section spectra were calculated. Efficient continuous wave laser operation was demonstrated with the crystal. A maximum output power of 7.7 W and slope efficiency of 60% were achieved at 1047 nm for the TEM00 mode.